P-197 Recruiting and retaining high quality staff – innovative solution to succession planning. (19th November 2022) - Mayo, Amanda; Richardson, Heather; Dodds, Nigel; O'Brien, Joanna; Watson, Mary
Abstract : Background: The ability to deliver high quality compassionate end of life care depends on recruiting and retaining high quality staff. Post COVID-19, organisations including hospices acknowledge significant national challenges in recruiting clinical staff with appropriate palliative care experience to meet increasingly complex needs. Innovative ways of succession planning are essential. We present an innovative project whereby aspiring Nurse Consultants are recruited to join an educational programme, incorporating the five pillars of advanced practice, underpinned by robust capabilities. We invite aspiring nurse consultants from other palliative care organisations across the UK to join the programme to benefit from shared learning and development. It encourages co-creation of learning opportunities with the aspiring Nurse Consultants. Aims: In our presentation we will explore the advantages/challenges of developing a contemporary programme of education and support for aspiring Nurse Consultants, as a prototype to develop consultant nurses of the future who can fill the requirement for consultant level input to hospice and broader palliative care workforces. The paper considers how this programme might be upscaled. Approach: An initial cohort of three aspiring Nurse Consultants at St Christopher's will be joined by further candidates to start a formal programme of learning, augmented by in-role support and reflection. All attend to clinical practice, service development, leadership, research and QI. The detail of the approach reflects seminal work by Manley, Taylor and Canadian capabilities related to the delivery of palliative care. Results: We will report on progress related to recruitment, the detail of the programme, development of the community of practice to which all participants will join and any learning along the way. Also, our insights regarding the value of such a course to support the increasing need for high quality end of life care as detailed in the Long-Term Plan and the Health and Social Care White Paper.